Differentiation of service offerings to corporate clients: theory and implications for a medium-sized Belarusian bank - Burakov, Vladimir (2005)
In this dissertation, the problem of differentiation of service offerings to corporate clients is considered from the marketing perspective where the main focus put on understanding of customers’ needs.